2018
DOI: 10.7717/peerj.5609
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarettes versus nicotine patches for perioperative smoking cessation: a pilot randomized trial

Abstract: IntroductionCigarette smoking by surgical patients is associated with increased complications. E-cigarettes have emerged as a potential smoking cessation tool. We sought to determine the feasibility and acceptability of e-cigarettes, compared to nicotine patch, for perioperative smoking cessation in veterans.MethodsPreoperative patients were randomized to either the nicotine patch group (n = 10) or the e-cigarette group (n = 20). Both groups were given a free 6-week supply in a tapering dose. All patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 27 publications
1
84
0
Order By: Relevance
“…A clinical trial comparing ENDS with traditional nicotine replacement patches for perioperative smoking cessation found that both methods were similarly effective. 23 Biochemically verified smoking cessation for 2 days preoperatively was achieved in 20% of patients in the nicotine patch group compared with 15% in the ENDS group ( P ≥ .999). Quit rates at 30 days postoperatively were 30% and 25%, respectively, which is similar to rates published using other cessation strategies.…”
Section: Smoking Cessation Strategiesmentioning
confidence: 90%
“…A clinical trial comparing ENDS with traditional nicotine replacement patches for perioperative smoking cessation found that both methods were similarly effective. 23 Biochemically verified smoking cessation for 2 days preoperatively was achieved in 20% of patients in the nicotine patch group compared with 15% in the ENDS group ( P ≥ .999). Quit rates at 30 days postoperatively were 30% and 25%, respectively, which is similar to rates published using other cessation strategies.…”
Section: Smoking Cessation Strategiesmentioning
confidence: 90%
“…associated with significantly increased smoking cessation in randomized clinical trials of e-cigarettes as smoking cessation therapy. Nine RCTs [16][17][18][19][73][74][75][76][77] were included for analysis. In 7 of the 9…”
Section: Provision Of Free E-cigarettes Wasmentioning
confidence: 99%
“…RCTs, the control group was provided free cessation aids 16,17,19,73,74,76,77 ; 2 RCTs provided the control group with smoking cessation counseling only. 18,75 In Figure 4 and Table 2).…”
Section: Provision Of Free E-cigarettes Wasmentioning
confidence: 99%
See 1 more Smart Citation
“…This precautionary approach towards electronic cigarettes has been echoed in policy documents and recommendations from medical and health authorities in Australia citing concerns about the unknown health risks of electronic cigarettes for the general population [ 34 , 35 , 36 , 37 ]. However, this approach may place limitations on the use of electronic cigarettes in specific clinical populations and scenarios, such as around the time of surgery to reduce the perioperative harm caused by tobacco smoking [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%